PENGARUH BEBAN PAJAK TANGGUHAN, CORPORATE GOVERNANCE DAN TRANSFER PRICING TERHADAP PENGHINDARAN PAJAK - Rani Arviani; Wiwit Setyawati (Jurnal Nusa Akuntansi, 2025)
The research aims to analyze the influence of Deferred Tax Expanse, Corporate Governance, and Transfer Pricing on Tax Avoidance. This research was conducted on non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019 to 2023, consisting of 55 data. The sample was taken using a purposive sampling technique, resulting in a sample of 11 companies with observations for 5 (five) years. The data used in this study are secondary data in the form of financial reports from each company that has been used as a research sample. The data analysis method uses panel data regression analysis. The test tool used is the E-Views 12 program. Based on the results of hypothesis testing, it is shown that Deferred Tax Expanse, Corporate Governance, and Transfer Pricing simultaneously have a significant effect on Tax Avoidance. Partially, only Deferred Tax Expense has a significant effect on Tax Avoidance, while Corporate Governance and Transfer Pricing do not have a significant effect on Tax Avoidance